2020
DOI: 10.1007/s11196-020-09711-y
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Dissent in Judicial Opinions: A Comparative, Genre-Based Analysis

Abstract: To date, there has been surprisingly little research on separate opinions in legal linguistics literature. Scarce attention has been paid to the linguistic and communicative aspects of how judges frame their disagreements. This paper serves as one of the early attempts to examine the institution of votum separatum, or separate opinion, from a comparative, cross-language perspective using a linguistic methodology. The evidence indicates a clear similarity in terms of how separate opinions are integrated within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…I collected data from two open domain sources: the Cornell Legal Information Institute (as in Goźdź-Roszkowski, 2020), and FindLaw.Com (as in Goźdź-Roszkowski, 2017). I collected 40 post-Roe and Doe SCOTUS opinions concerning abortion (217,685 words in total).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…I collected data from two open domain sources: the Cornell Legal Information Institute (as in Goźdź-Roszkowski, 2020), and FindLaw.Com (as in Goźdź-Roszkowski, 2017). I collected 40 post-Roe and Doe SCOTUS opinions concerning abortion (217,685 words in total).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, as already stated, just a few studies have examined separate opinions. For example, Goźdź-Roszkowski (2020) comparatively examines dissents in Poland’s supreme judicial body and SCOTUS. McKeown (2021) examines SCOTUS majority and dissent opinions.…”
Section: Scotus Opinion Writing and Judicial Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have even suggested that specific genres may be assigned specific translation strategies for specific language pairs (Arntz 1988: 468), although no conclusive results have been produced in this sense (see Mayoral Asensio 2002 for a critique of this point). Substantial research efforts have been devoted to finding the key elements that distinguish one genre from another as a basis for classification (Emery 1991, Goźdź-Roszkowski 2020, House 1977, Reiß 1982, Sandig 1972, Schmidt 1993, Wilss & Thome 1984. Descriptions of genres relevant to translation have mainly focused on specialized domains and provided substantial data to increase our knowledge of discourse across languages and cultures (among many others, Moreno-Pérez 2020; Orts 2015; Pontrandolfo 2014).…”
Section: Genre: Socially Developed Historically and Cognitively Rootedmentioning
confidence: 99%
“…Несмотря на это, спустя 20 лет, этот пробел так и не был устранен в федеральном законе, о чем в своем мнении указывает судья Н.С. Бондарь 14 Судья Г.А. Гаджиев 18 очень подробно и последовательно изложил свою позицию в понимании принципа «in dubio contra fi scum» (сомнение против фиска), а также когда и при каких условиях должен применяться пункт 7 статьи 3 Налогового Кодекса РФ.…”
unclassified